A piezoelectric poly(vinylidene fluoride) tube featuring highly-sensitive and isotropic piezoelectric output for compression. Issue 2 (4th January 2021) - Guo, Jiajun; Nie, Min; Wang, Qi
Abstract : A PVDF tube exhibited a highly-sensitive and isotropic piezoelectric output for multi-stresses from any directions. Abstract : Piezoelectric polymers have aroused tremendous attention in self-powered flexible wearable electronics. However, conventional plate-like piezoelectric devices demonstrated insufficient output power and monotonous piezoelectric energy harvesting performance only in one direction, failing to accommodate the complex multi-dimensional stress field. In this study, a poly(vinylidene fluoride) tube featuring all-directional piezoelectric energy harvesting performance with excellent rebound resilience was prepared via a fast industrial extrusion. Benefitting from the isotropic hollow tubular structure, the piezoelectric tube experienced large deformation at a small external load and thus exhibited a strong load-amplifying function to generate the optimized output power at multi-stresses from any direction, with sensitive piezoelectric performance, quick response and mechanical robustness. Finally, the practical potential as a robust energy harvester was evaluated by harvesting small energy from irregular human motions. This study provides a facile structure designing strategy for the preparation of functional piezoelectric devices for multi-directional mechanical energy harvesting applications.